Beyond the blue fence: Inequalities and spatial segregation in the development of the London 2012 Olympic media event. Issue 2 (1st June 2014) - Finlay, Christopher
This article presents two cases studies of local resistance to the conscious effort of Olympics actors to use East London as representational space to produce and reinforce dominant nationalist and neo-liberal themes in the 2012 Olympic media event narrative. The blue Olympic fence, a 17.5-kilometre plywood barrier that encased the Olympic Park construction site, is used as a device in both case studies to explore the production and contestation of discourses of Olympic space. It is argued that the blue fence is both the subject and object of discourse about the purposes, values, impacts and flows of Olympics-led development. The first case study is an analysis of alternative representations of East London produced by local political leaders who found themselves on the wrong side of the blue fence and frustrated by the weak community engagement efforts of Olympic organizers. The second case study is an analysis of digital and transmedia projects and texts produced by local East London residents in response to the Olympic blue fence and the Olympic narrative it stood for.